2008
DOI: 10.1149/1.2820627
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of Li[sub x]Ti[sub y]Mn[sub 1−y]O[sub 2] (y=0, 0.11) Electrode Materials with Pyrrolidinium-Based Ionic Liquid Electrolyte Systems

Abstract: The possibility of using electrolyte systems based on room-temperature ionic liquids ͑RTILs͒ in lithium-battery configurations is discussed. The nonflammability and wide potential windows of RTIL-based systems are attractive potential advantages, which may ultimately lead to the development of safer, higher energy density devices than those that are currently available. An evaluation of the compatibility of these electrolyte systems with candidate electrodes is critical for further progress. A comparison of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
75
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 32 publications
9
75
0
Order By: Relevance
“…[16][17][18] At a platinum electrode, mixtures of C 3 mpyrFSI and LiTFSI not only display reversible lithium electrochemistry, 14 but the behavior is also characterized by a shift of Ͼ1 V in the cathodic reduction limit for the electrolyte. 19 This is consistent with the behavior expected when both Li + and TFSI − ions are present ͑see above͒.…”
supporting
confidence: 86%
“…[16][17][18] At a platinum electrode, mixtures of C 3 mpyrFSI and LiTFSI not only display reversible lithium electrochemistry, 14 but the behavior is also characterized by a shift of Ͼ1 V in the cathodic reduction limit for the electrolyte. 19 This is consistent with the behavior expected when both Li + and TFSI − ions are present ͑see above͒.…”
supporting
confidence: 86%
“…In the meantime, given to the actual high cost, it is likely that ILs, rather than full electrolyte media, will be used as additives to the common organic liquid electrolyte solutions [51,52].…”
Section: Improvements In Safety and Reliabilitymentioning
confidence: 99%
“…6,7 Partial substitution appears to impart resistance against dissolution and degradation of the material in electrochemical cells with LiPF 6 -containing electrolytic solutions at elevated temperature. 5 Saint et al 8 have also observed a similar protective effect in cells with pyrrolidinium-based ionic liquid electrolytes; Li x MnO 2 undergoes rapid capacity fading due to an electrochemically induced dissolution/precipitation reaction whereas and SS-or GNC-Li x Ti 0.11 Mn 0.89 O 2 to specify which of the sodium-containing precursors was used in their preparation.…”
Section: Introductionmentioning
confidence: 80%